A Compact Two-Loudspeaker Virtual Sound Reproduction System for Clinical Testing of Spatial Hearing With Hearing-Assistive Devices - Hamdan, Eric C.; Fletcher, Mark D. (Frontiers in Neuroscience, 2022)
Exciting developments in hearing aid and cochlear implant technology for linking signal processing across the ears have improved spatial hearing outcomes. This has resulted in an increased emphasis on clinical assessment of the spatial hearing abilities of hearing-assistive device users. Effective assessment of spatial hearing currently requires a large and costly loudspeaker array system, housed in a heavily acoustically treated testing room. This imposes economic and logistical constraints that limit proliferation of array systems, particularly in developing nations. Despite their size and cost, the ability of current clinical array systems to reproduce realistic spatial sound fields is limited, which substantially reduces the range of realistic acoustic scenes that can be used for diagnostic testing. We propose an alternative low-cost, compact virtual acoustics system with just two loudspeakers. This system uses crosstalk cancelation to reproduce pressure signals at the device microphones that match those for real-world sound sources. Furthermore, in contrast to clinical array systems, the system can adapt to different room acoustics, removing the requirement for a heavily acoustically treated testing environment. We conducted a proof-of-concept study in two stages: in the first, we evaluated the physical performance of the system for a stationary listener in anechoic conditions and in a small audiological testing booth with moderate acoustic treatment. To do this, a head and torso simulator was fitted with specially adapted hearing-assistive devices that allowed direct access to the microphone signals. These microphone signals were compared for real and virtual sound sources at numerous source locations. In the second stage, we quantified the system’s robustness to head rotations with and without the system adapting for head position. In the stationary case, the system was found to be highly effective at reproducing signals, such as speech, at all tested source locations. When head rotation was added, it performed well for rotations of up to 2°, even without adapting. However, performance improved markedly for larger rotations when the system adapted. These findings suggest that a compact, low-cost virtual acoustics system can give wider access to advanced and ecologically valid audiological testing, which could substantially improve clinical assessment of hearing-assistive device users.